Legal Issues Regarding the Reproductive Rights of Single Women in China - Zhu, Yike (Transactions on Social Science, Education and Humanities Research, 2025)
As a basic human right, the right to reproduce is a fundamental right for citizens to freely decide on their reproductive behavior. However, under the influence of traditional family ethics and the logic of social governance, the reproductive rights of single women have long been in an ambiguous zone of legal protection. With changes in social attitudes, demographic restructuring, and the growing awareness of women’s independence, the legitimacy and reality of single women’s reproductive rights have gradually become the focus of social attention. This paper will combine legal theory, judicial practice and social reality, and adopt the methods of comparative analysis, case analysis and literature analysis to explore the path of legal protection of single women’s reproductive rights and the challenges they face. Through a comparative analysis of the legal provisions and legal safeguards for the reproductive rights of single women in China and the United States, to gain a clearer understanding of the attitudes and practices of this right under different legal systems. It is also proposed that reasonable boundaries should be set, the rights and autonomy of single women should be respected, and that overseas experience in the rule of law should be drawn upon, so as to provide a reference for the improvement of the relevant legal system in China.